Mambo goddess - Kozic, Maria; Mambo (Firm) ([Sydney] : Mambo Graphics P/L, 1997)
Poster featuring a woman with flowing orange hair, wearing a pink dress. There are wolves lower left and right. The title appears in orange text at the upper edge. The background is purple.
Caption title.
Digital master available
Keywords: Women -- Posters; Wolves -- Posters; Posters, Australian; Australia -- Posters; Australian